Potensi dan Strategi Pengembangan Usaha Tani Perkotaan dalam Meningkatkan Akses Pangan yang Berkelanjutan di Kecamatan Gunung Putri, Kabupaten Bogor - Nia Kurniawati Hidayat; Ahyar Ismail; Hastuti; Fitria Dewi Raswatie (Institut Pertanian Bogor, 2022)
As a densely populated industrial area in Bogor Regency, an urban farming program has been initiated in Gunung Putri District. The right strategy to develop and implement urban farming needs to be known so that this program is successful and sustain in Bogor Regency. This study aims to (1) identify aspects of preparation for urban farming development in Gunung Putri District, Bogor Regency; (2) analyze people's perceptions of its development; (3) and formulate its development strategy through qualitative descriptive methods, Likert scale, and SWOT analysis. Based on technical, social, institutional, commercial, financial, and environmental aspects, urban farming activities in this location are potential to be developed to support food adequacy and contribute to household income. The society has an excellent perception of the benefits. However, the community also saw obstacles, including the availability of respondents' time, usable land, capital, and supportive institutions. Most respondents also perceived that the currently limited information related to marketing has the potential to hinder the successful implementation of the urban farming. Nevertheless, the community's desire to participate is quite high, and they will participate if the program is implemented. The highest strength factor in developing urban farming businesses in Gunung Putri District is the public knowledge about cultivation techniques, while the most significant weakness is the marketing of its products. An enormous opportunity is to establish networking with various parties, and the biggest threat is the trend of urban life that does not focus on the agricultural sector. Keywords: aspects of feasibility, community perception, urban farming, SWOT analysis